Lowering of fasting and food stimulated serum immunoreactive gastric inhibitory polypeptide (GIP) by glucagon. Issue 2 (February 1977) - Ebert, R; Arnold, R; Creutzfeldt, W
Abstract : The effect of intravenous glucagon infusion on serum levels of immunoreactive GIP (IR-GIP), insulin (IRI), gastrin (IRG), and on blood glucose has been investigated in six healthy volunteers in the fasting state and during ingestion of a mixed standard meal. Glucagon (500 ng/kg/min) lowered significantly serum levels of IR-GIP and IRG below the fasting values and increased the levels of IRI and blood glucose. Glucagon (50 ng/kg/min) infused 30 minutes before and continued 90 minutes after ingestion of a test meal abolished the IR-GIP response, suppressed significantly the IRG response, and left the IRI response unchanged. The same glucagon dose infused 60 minutes after ingestion of the test meal decreased significantly the raised levels of IR-GIP and IRG to fasting levels without changing IRI values. It is concluded that exogenous glucagon inhibits Gip release at the level of the GIP-producing cells.